COMPARISON OF EXCEPTIONAL GREAT NUMBERS OF MEROMORFNIH FUNCTIONS CAPACITY - Савчук, Ярослав Іванович; Овчар, Ігор Євгенійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A question about distributing of values of meromorphic functions of calculated order is examined. It is shown, that the great number of exceptional values in understanding G. Valiron can have power continuum.